Interventions to treat cutaneous leishmaniasis in children: A systematic review. - Andrés Uribe-Restrepo; Alexandra Cossio; Mayur M Desai; Diana Dávalos; María Del Mar Castro (Public Library of Science (PLoS), 2018)
BACKGROUND:Case management in children with cutaneous leishmaniasis (CL) is mainly based on studies performed in adults. We aimed to determine the efficacy and harms of interventions to treat CL in children. METHODS:We conducted a systematic review of clinical trials and cohort studies, assessing treatments of CL in children (≤12 years old). We performed structured searches in PubMed, CENTRAL, LILACS, SciELO, Scopus, the International Clinical Trials Registry Platform (ICTRP), clinicaltrials.gov and Google Scholar. No restrictions regarding ethnicity, country, sex or year of publication were applied. Languages were limited to English, Spanish and Portuguese. Two reviewers screened articles, completed the data extraction and assessment of risk of bias. A qualitative summary of the included studies was performed. RESULTS:We identified 1092 records, and included 8 manuscripts (6 Randomized Clinical Trials [RCT] and 2 non-randomized studies). Most of the articles excluded in full-text review did not report outcomes separately for children. In American CL (ACL), 5 studies evaluated miltefosine and/or meglumine antimoniate (MA). Their efficacy varied from 68-83% and 17-69%, respectively. In Old-World CL (OWCL), two studies evaluated systemic therapies: rifampicin and MA; and one study assessed efficacy of cryotherapy (42%, Per Protocol [PP]) vs intralesional MA (72%, PP). Few studies (4) provided information on adverse events (AEs) for children, and no serious AEs were reported in participants. Risk of bias was generally low to unclear in ACL studies, and unclear to high in OWCL studies. CONCLUSION:Information on efficacy of treatment for CL in children is scarce. There is an unmet need to develop specific formulations, surveillance of AEs, and guidelines both for the management of CL and clinical trials involving the pediatric population. REGISTRATION:The protocol of this review was registered in the PROSPERO International register of systematic reviews, number CRD42017062164.